RETROSPECTIVE DATA REVIEW TO FIND THE ASSOCIATION OF LUMBOSACRAL TRANSITIONAL VERTEBRA AND DEGENERATIVE DISC DISEASE IN YOUNG PATIENTS - Gul, Nadia; Mehmood, Khalid; Ikram, Muhammad (Pakistan Armed Forces Medical Journal, 2020)
Objective: To find out the frequency of lumbar disc degeneration among the patients having lumbosacraltransitional vertebra between 20-40 years.Study Design: Retrospective cross sectional study.Place and Duration of Study: Radiology department POF Wah Cantt, from Jan 2018 to Dec 2019.Methodology: Six Hundred patients between 20-40 years having lumbosacral transitional vertebra and historyof low back pain >1 year were studied. X ray and MRI lumbar spine of these patients was studied retrospectivelyon PACS. Two hundred patients having history of traumatic or other non-traumatic etiologies, in addition toLumbosacral transitional vertebra were excluded. Four hundred patients with only lumbosacral transitionalvertebra were included. Data analysis was done by SPSS-22. Castellvi types of transitional vertebra was calculated among patients with degenerative lumbar disc.Results: One hundred and four (26.6%) were having degenerative disc disease while 296 (74.4%) patients werenot having degenerative disc disease. Patients having degenerative disc disease were between 24-40 years withthe mean age 29.96 ± 0.417 years. Among the patients having degenerative disc disease were 59 women and45 males but no statistical significance association was found between gender and degenerative disc disease with p-value = 0.55. Castellvi type III had significant association with degenerative disc disease, p-value = 0.006.Conclusion: Age related disc degeneration is commonly seen in middle age people but in younger age group in2nd and 3rd decade it is observed frequently in those patients having lumbosacral transitional vertebra especially in the setting of no other associated traumatic or non-traumatic etiology, which leads to early degenerative disc disease.